Enhanced stability, bistability, and exceptional points in saturable active photonic couplers - Yertay Zhiyenbayev; Yannis Kominis; Constantinos Valagiannopoulos; Vassilios Kovanis; Anastasios Bountis (American Physical Society, 2019)
A generic photonic coupler with active and lossy parts, gain saturation, and asymmetric characteristics is examined. Saturable activity enhances the overall stability of steady states, prevents evolution to undesirable unbounded modes, and allows bistable operation in specific parameter regions. Both stability and bistability are analyzed in phase space, with identified basins of attraction. Continuous families of exceptional points are detected through appropriate tuning of coupling and asymmetry, offering a comprehensive description of the nonlinear dynamics—with implications for various application-driven designs.
Keywords: saturable activity photonic couplers stability bistability exceptional points